2016
DOI: 10.1245/s10434-016-5227-y
|View full text |Cite
|
Sign up to set email alerts
|

From Conventional Radiotracer Tc-99m with Blue Dye to Indocyanine Green Fluorescence: A Comparison of Methods Towards Optimization of Sentinel Lymph Node Mapping in Early Stage Cervical Cancer for a Laparoscopic Approach

Abstract: The fluorescence SLN mapping with ICG achieved a significantly higher detection rate and bilateral mapping compared to standard radiocolloid and BD technique in women with early stage cervical cancer. Nodal staging with an intracervical injection of ICG is accurate, safe, and reproducible in patients with cervical cancer. Before replacing lymphadenectomy completely, the additional value of fluorescence SLN mapping on both perioperative morbidity and survival should be explored and confirmed by ongoing controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 29 publications
(29 reference statements)
5
53
0
2
Order By: Relevance
“…The greatest advantage of the ICG fluorescence imaging system is that it allows visualization of SN and afferent lymphatic vessels from primary tumor sites more clearly than a conventional dye approach based on visual recognition without special tools. To date, several investigators have demonstrated the clinical benefit of the ICG fluorescence imaging approach for SN detection in patients with several malignancies, including gastric cancer 16, 17, 18, 19…”
Section: A Novel Imaging System Developed For Sn Detectionmentioning
confidence: 99%
“…The greatest advantage of the ICG fluorescence imaging system is that it allows visualization of SN and afferent lymphatic vessels from primary tumor sites more clearly than a conventional dye approach based on visual recognition without special tools. To date, several investigators have demonstrated the clinical benefit of the ICG fluorescence imaging approach for SN detection in patients with several malignancies, including gastric cancer 16, 17, 18, 19…”
Section: A Novel Imaging System Developed For Sn Detectionmentioning
confidence: 99%
“…Nodal staging with an intracervical injection of ICG has also been established as accurate, safe, and reproducible in patients with cervical cancer 8,9…”
Section: Resultsmentioning
confidence: 99%
“…Overall ICG remains a very safe product that performs better than the other conventional tracers (such as Tc-99m and blue dyes alone or in combination) when adopted for the SLN mapping in gynecologic oncology [2][3][4][5][6]8]. Although adverse reactions resulting from an intravenous or an interstitial injection of ICG are expected to be the same, since ICG has only been approved by FDA for intravenous injection, it is crucial to inform the patients undergoing SLN mapping on its off-label use as adverse reactions may otherwise lead to unpleasant medico-legal consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for an easy identification of the SLN. In gynecologic oncology this tracer has proven to be at least equivalent to the combination of technetium-99m Tc-99m and blue dyes as far as detection rates goes [2][3][4][5][6]. ICG seems to perform better in obese patients and is user friendlier as it does not require a preoperative intracervical injection as is the case with Tc-99m.…”
Section: Introductionmentioning
confidence: 99%